Infer with care: A critique of the argument from animals - Brown, Rachael L. (Mind & Language, 2019)
Non‐human animal evidence is frequently invoked in debates in cognitive science. Here, I critically assess one use of such evidence in the form of the “argument from animals,” a prominent positive argument for nativism, which roughly states that non‐human cognitive development is largely nativist, and thus human cognitive development is most likely largely nativist too. I offer a number of reasons to reject this argument, and in doing so derive some important broader lessons concerning the appropriate role of non‐human animal evidence in a science of the human mind.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTExMS9taWxhLjEyMTkw